Effects of CpG islands DNA methylation on the human choline kinase alpha promoter activity - Sa'dom, Siti Aisyah Faten Mohamed (2021)
Choline kinase (CK) is a cytosolic enzyme catalyzing the phosphorylation of choline to phosphocholine (PCho) in the biosynthesis of phosphatidylcholine (PC), a major component of membrane phospholipid. Despite the importance of CK in PC biosynthesis, cell growth and carcinogenesis, little is known about the transcriptional regulation of ckα gene. The presence of CpG islands on the promoter region of ckα gene suggests the involvement of DNA methylation in its transcriptional control. Therefore, this study aimed to investigate the effects of CpG islands DNA methylation on ckα gene promoter activity. A 2009 bp promoter region of the human ckα gene was cloned into a firefly luciferase reporter vector (pGL4.10) to create a recombinant plasmid, pGL4.10-ckα (-2000/+9). Then, a series of CpG island deletion mutants were constructed using PCR site-directed mutagenesis method and cloned into pGL4.10 vector and studied in human breast adenocarcinoma, MCF-7 cells. The methylation status after treatment with a demethylating agent, 5-azacytidine and re-methylating agent, budesonide showed a prominent role of DNA methylation of ckα gene promoter in MCF-7 cancer cells compared to the corresponding normal cells MCF10A. A total of four CpG islands were identified within the promoter region by using MethPrimer and EMBOSS CpGPlot software. Deletion of the region between -225 to -56 bp in the fourth CpG island showed an increased promoter activity as compared to the full-length promoter indicating the presence of important negative regulatory elements which could be modulated by DNA methylation. An in vitro methylation analysis showed the methylated full-length promoter activity was significantly lower than the methylated fourth CpG island deletion suggesting that this CpG island contains elements for the binding of suppressor transcription factors. Mutation of MZF1 binding site in the fourth CpG island caused a significant increase in the ckα promoter activity, suggesting a repressive role of this sequence element. EMSA analysis showed that there is a binding of transcription factor to the MZF1 binding site, and the cytosine methylation at this site showed an increase of the binding of this putative MZF1 transcription factor at -181 to -175 ckα promoter region. Furthermore, mutation of MZF1 binding site abolished the protein-DNA formation complex. These results suggest that DNA methylation decreased the ckα promoter activity by promoting the binding of MZF1 transcription factor to the fourth CpG island located at -225 to -56 region. In conclusion, this study provides a perspective on the involvement of CpG island and DNA methylation in the transcriptional control of cka gene.